2018
DOI: 10.21037/jtd.2018.01.70
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum leptin levels and pulmonary tuberculosis: a meta-analysis

Abstract: In conclusion, our present findings suggest that decreased serum leptin levels may be associated with the pathogenesis of PTB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Leptin-deficient mice and mice rendered leptin-deficient by fasting exhibit impaired pulmonary bacterial clearance (Table 1 ) and enhanced lethality during pulmonary tuberculosis, bacterial pneumonia, and sepsis ( 30 32 ). The patients with pulmonary tuberculosis (PTB) have decreased serum leptin levels, and an increase in adiponectin may serve as a reliable biomarker for predicting the development and progression of PTB pathogenesis ( 111 , 145 , 146 ). Mycobacterium infection in ob/ob mice was hampered to produce organized granulomatous response and defective in CD4+ and CD8+ T cells functions, IFN-γ and DTH responses ( 30 ).…”
Section: Leptin and Bacterial Infectionsmentioning
confidence: 99%
“…Leptin-deficient mice and mice rendered leptin-deficient by fasting exhibit impaired pulmonary bacterial clearance (Table 1 ) and enhanced lethality during pulmonary tuberculosis, bacterial pneumonia, and sepsis ( 30 32 ). The patients with pulmonary tuberculosis (PTB) have decreased serum leptin levels, and an increase in adiponectin may serve as a reliable biomarker for predicting the development and progression of PTB pathogenesis ( 111 , 145 , 146 ). Mycobacterium infection in ob/ob mice was hampered to produce organized granulomatous response and defective in CD4+ and CD8+ T cells functions, IFN-γ and DTH responses ( 30 ).…”
Section: Leptin and Bacterial Infectionsmentioning
confidence: 99%
“…Falling leptin concentrations appeared to be responsible for reduced T-cell function during starvation (24). A recent meta-analysis of twelve case-control studies found serum leptin levels of healthy controls were markedly higher than those of pulmonary tuberculosis patients (25), and after treatment of TB plasma leptin levels were observed to increase (26). However, the correlation between leptin and VD in TB patients has not been reported until now.…”
mentioning
confidence: 98%
“…The thousand faces of leptin thus make it difficult to target, as it acts as a rheostat, depending on the trigger, ranging from a protective cytokine-like hormone to a harmful molecule (Table 1). 11,23,28,37,40,42,[46][47][48]59,61,66,75,79,82,85 Under physiological conditions, leptin clearly appears to control lung development and maturation at the fetal stage, as well as normal lung homeostasis, from lung ventilation to the bronchial diameter following birth and throughout adulthood. In lung infections, leptin appears to act as a protective cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, another more recent study found a significant association between higher plasma leptin levels and a higher risk of respiratory infections of greater severity in a cohort of ambulatory patients, independent of BMI and other established risk factors. 47 In TB, studies have shown that leptin levels are lower in patients with TB than in control subjects 48 and that thin subjects are more susceptible to develop active TB, whereas obesity is associated with a lower risk of pulmonary TB. 49 Thus, a decrease in the production of leptin during active TB may be a factor in the severity of the disease, especially in thin patients.…”
Section: Leptin and Physiological Respiratory Functionsmentioning
confidence: 99%